Pertanggungjawaban Pidana terhadap Pelaku Kekerasan Pacaran (Dating Violence) menurut Hukum Pidana di Indonesia - Miftah Fauziyya Rahma; Lilis Purba (Decisio: Jurnal Ilmiah Hukum, 2026)
This study examines criminal liability for perpetrators of dating violence in Indonesia. The phenomenon of dating violence is increasing, particularly among adolescents and young adults, with various forms including physical, psychological, sexual, and economic violence. However, there are no regulations explicitly addressing dating violence as a separate crime.The results of this study indicate that dating violence can be prosecuted under various general criminal law provisions, such as Article 351 of the Indonesian Criminal Code concerning assault, Article 285 of the Indonesian Criminal Code concerning rape, and provisions in Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS). The form of criminal liability for perpetrators is determined based on the type of violence committed, the motive, and the resulting consequences. The main obstacles to law enforcement are the lack of specific regulations on dating violence, difficulties in establishing evidence, and low awareness among victims about reporting. Therefore, strengthening regulations and increasing public legal awareness are needed to achieve better legal protection for victims.